The Effect of Knowledge Management in Healthcare Services: A Systematic Review - Ayatulloh, Daviq; Nursalam, Nursalam; Kurniawati, Ninuk Dian (Universitas Pendidikan Indonesia, 2021)
Introduction : The quality of service at health facilities needs to be improved, one of the main keys is the service provided by health workers. Objective : The aim of this systematic review was to analyze the effectiveness of knowledge management in healthcare. Methods : The systematic review was carried out in March-April 2020 with a range of article search times from 2016-2020 using 5 electronic databases (Scopus, PubMed, Science Direct, CINAHL and ProQuest). The Center for Review and Dissemination and the Joanna Briggs Institute Guideline were used to assess the quality and PRISMA's checklist for this review guide. The literature search described four keyword groups based on Medical Subject Heading (MeSH) and the search description was (knowledge management*' OR 'SECI knowledge management') AND ('health care' OR hospital). Result : The article searched was found 13 articles suitable with the eligibility criteria, the results of the systematic review found that knowledge management had the effectiveness to provide information and knowledge processes, improve decision-making abilities, improve performance and quality of health services and increase organizational effectiveness. Discussion : As health service providers, hospitals and other health care institutions must continue to improve the quality of services. By improving the quality of services, it is expected to be able to answer the demands of the community to always provide optimal health services. With the application of good knowledge management, ideas and creativity from the workforce will be created in creating health service innovations.Â ABSTRAKPendahuluan : Kualitas pelayanan di fasilitas kesehatan perlu ditingkatkan, salah satu kunci utamanya adalah pelayanan yang diberikan oleh tenaga kesehatan. Tujuan : Tujuan dari tinjauan sistematis ini adalah untuk menganalisis efektivitas manajemen pengetahuan dalam perawatan kesehatan. Tinjauan sistematis dilakukan pada bulan Maret-April 2020 dengan rentan waktu pencarian artikel adalah 2016-2020 menggunakan 5 database elektronik (Scopus, PubMed, Science Direct, CINAHL dan ProQuest). Center for Review and Dissemination dan Joanna Briggs Institute Guideline digunakan untuk menilai kualitas dan daftar periksa PRISMA untuk panduan ulasan ini. Pencarian literatur menggambarkan empat kelompok kata kunci berdasarkan Medical Subject Heading (MeSH) dan deskripsi pencarian adalah (manajemen pengetahuan*' ATAU 'manajemen pengetahuan SECI') AND (efek ATAU dampak ATAU) DAN ('perawatan kesehatan' ATAU rumah sakit). Â Hasil : Artikel yang dicari ditemukan 13 artikel yang sesuai dengan kriteria kelayakan, hasil tinjauan sistematis menemukan bahwa manajemen pengetahuan memiliki efektivitas untuk memberikan informasi dan proses pengetahuan, meningkatkan kemampuan pengambilan keputusan, meningkatkan kinerja dan kualitas pelayanan kesehatan dan meningkatkan organisasi efektivitas. Diskusi : Sebagai penyelenggara pelayanan kesehatan, rumah sakit dan institusi pelayanan kesehatan lainnya harus terus meningkatkan kualitas pelayanan. Dengan peningkatan mutu pelayanan diharapkan mampu menjawab tuntutan masyarakat untuk selalu memberikan pelayanan kesehatan yang optimal. Dengan penerapan manajemen pengetahuan yang baik akan tercipta ide dan kreativitas dari tenaga kerja dalam menciptakan inovasi pelayanan kesehatan.